2001
DOI: 10.1074/jbc.m100506200
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of SppA, a Novel Light-inducible Chloroplast Protease Complex Associated with Thylakoid Membranes

Abstract: A new component of the chloroplast proteolytic machinery from Arabidopsis thaliana was identified as a SppA-type protease. The sequence of the mature protein, deduced from a full-length cDNA, displays 22% identity to the serine-type protease IV (SppA) from Escherichia coli and 27% identity to Synechocystis SppA1 (sll1703) but lacks the putative transmembrane spanning segments predicted from the E. coli sequence. The N-terminal sequence exhibits typical features of a cleavable chloroplast stroma-targeting seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
68
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 68 publications
1
68
0
Order By: Relevance
“…SppA is a light stress-induced, thylakoidbound, ATP-independent Ser-type protease with unknown substrates (Lensch et al, 2001). Interestingly, the very abundant thylakoid FtsH protease complex (FtsH1, FtsH2, FtsH5, and FtsH8;Liu et al, 2010b;Kato et al, 2012), robustly quantified with many MS/ MS spectra (114, 499, 528, and 146 for FtsH1, FtsH2, FtsH5, and FtsH8, respectively; Supplemental Table S3), was not significantly affected (between 0.8-and 1.2-fold).…”
Section: Effects On Plastid Gene Expression and Protein Homeostasismentioning
confidence: 99%
“…SppA is a light stress-induced, thylakoidbound, ATP-independent Ser-type protease with unknown substrates (Lensch et al, 2001). Interestingly, the very abundant thylakoid FtsH protease complex (FtsH1, FtsH2, FtsH5, and FtsH8;Liu et al, 2010b;Kato et al, 2012), robustly quantified with many MS/ MS spectra (114, 499, 528, and 146 for FtsH1, FtsH2, FtsH5, and FtsH8, respectively; Supplemental Table S3), was not significantly affected (between 0.8-and 1.2-fold).…”
Section: Effects On Plastid Gene Expression and Protein Homeostasismentioning
confidence: 99%
“…There are published reports on a novel light-inducible chloroplast proteinase complex associated with thylakoid membranes, SppA, from Arabidopsis thaliana (a kind of plant, var. Landsberg erecta) 16) and light-dependent chloroplast metalloproteinase complex associated with thylakoid membranes, FtsH, from spinash leaves. 17) SppA is a light-inducible serine-type proteinase participating in the light-dependent turnover of thylakoid membrane proteins or of peptides released from such proteins under light stress conditions.…”
Section: Characteristics Of the Enzymementioning
confidence: 99%
“…17) SppA is a light-inducible serine-type proteinase participating in the light-dependent turnover of thylakoid membrane proteins or of peptides released from such proteins under light stress conditions. 16) FtsH proteinase takes part in degrading proteins whose synthesis and assembly are light-dependent. 17) Hence, the serine proteinase from Rvi.…”
Section: Characteristics Of the Enzymementioning
confidence: 99%
“…Furthermore, an overexpressed peptide with the N-terminal sequence of pea Lhcb1 has been shown to be degraded in vitro by a stromal serine-type glutamyl endopeptidase and by a cysteinetype enzyme attached to the thylakoid membrane (22). It has also been suggested that the SppA protease might be involved in the degradative regulation of LHC II apoproteins (23). However, the LHC II protease(s) have not been conclusively identified.…”
mentioning
confidence: 99%